Rancang Bangun Sistem Informasi Penyewaan menggunakan Metode Waterfall - Pebri Damayanti; Siti Masripah (Jurnal Sistem Informasi Akuntansi, 2021)
The rental is an agreement or agreement made by the two parties concerned during a predetermined period of time and at an agreed price. Today there are already many companies moving in the field of room rental services complete with its facilities, this makes many room rental services users perform room rentals for the purposes of the events they will implement. To that endeavor in this field desperately requires systems that can support to improve customer service. At this time there were still many companies moving in the field using still-manual systems, ranging from customers wishing to conduct room rentals having to go to the company. As for the record keeping of customer booking data still done manually can lead to customer rental schedule errors, a subscriber rental data redundancy occurs. The methods used to address such problems are the development of waterfall systems (Analyses of system needs, Design, Code Generation, Testing, Support) and web-based information systems. From the development of the system used can address problems such as the occurrence of rental schedule data errors and others, resulting in accurate information and the achievement of an effective and efficient activity